Prevalence and Predictors of Contraception Usage in Karachi, Pakistan - Siddiqui, Maheen (Cureus, 2020)
Background Contraception, also known as family planning, refers to methods that intercept unwanted pregnancies. The modalities of contraception have evolved and multiplied over time to facilitate users. Despite enormous benefits, the contraceptive methods remain underutilized in developing countries such as Pakistan. Accordingly, the primary purpose of our study is to determine the prevalence, perception, and attitude of contraceptive usage in Karachi. The study further assesses the knowledge and core determinants of contraception. Methods A cross-sectional study was conducted in Karachi, Pakistan. The sample population comprised currently married males and females residing in Karachi, with females from 16 to 45 years of age and males of 16 years of age and forth. Pregnant females, divorcees, and widowed individuals were excluded. A pre-tested questionnaire was administered to record the demographics, knowledge, and frequency of contraceptive usage, and attitude and perception towards contraception. The data were analyzed using the Statistical Package for the Social Sciences (SPSS( v. 23.0 (IBM Corp. Armonk, NY). Results Results depicted that 93.4% (n=468) had knowledge of contraception while 49.7% (n=249) were currently using contraception. The most frequently employed contraceptive modality emerged as condoms (n=163, 65.5%), followed by withdrawal (n=71, 28.5%) and pills (n=62, 24.9%). The prevalence of contraceptive usage was more inclined towards the educated stratum and higher socioeconomic class. Potential predictors for contraceptive usage came out as the number of children, knowledge regarding contraception, spouse’s support for usage, a desire for more children, and family planning counseling (p<0.05). Conclusion There is a drastic increase in the prevalence of contraceptive usage in Pakistan as compared to previous studies. Efforts must be made to further augment the knowledge and awareness regarding contraceptive modalities to increase acceptability and eliminate myths prevalent in society regarding contraception.